Aldehyde Dehydrogenase Polymorphisms and Blood Pressure Elevation in the Japanese: A Cross-Sectional and a Longitudinal Study over 20 Years in the Shimane CoHRE Study. (22nd June 2015) - Isomura, Minoru; Wang, Tao; Yamasaki, Masayuki; Hasan, Md. Zahid; Shiwaku, Kuninori; Nabika, Toru
Abstract : Purpose . Effects of a genetic polymorphism in the aldehyde dehydrogenase-2 ( ALDH2 ) on blood pressure (BP) were investigated in a cross-sectional and a longitudinal study over 20 years on Japanese rural residents. Methods . Health examinations were held through 2006 to 2012, and 3, 202 participates were recruited for this study. Among these participants, 560 individuals had medical records that were obtained in a health examination 20 years ago. Genomic DNA of participants was extracted from blood and the genotype of a polymorphism in ALDH2 was determined by the TaqMan method. Multivariate regression analyses were performed to examine association between BP and the genetic polymorphism in the ALDH2 gene. Results . Systolic and diastolic BP were higher in the ALDH2 ∗ 1 / ∗ 1 than the others ( ALDH2 ∗ 1 / ∗ 2 or ALDH2 ∗ 2 / ∗ 2 ). Genetic variation of the ALDH2 gene apparently influenced drinking behavior as the number of the drinkers was significantly reduced in the ALDH2 ∗ 2 / ∗ 2 after 20 years of the observation period. This polymorphism, however, did not confer a risk for BP increase in the longitudinal observation. Conclusion . The present cross-sectional study confirmed a genetic effect of the ALDH2 gene on BP. In contrast, no significant effects on BP were identified in a longitudinal study, which may require a careful consideration.